2015
DOI: 10.1515/helia-2015-0012
|View full text |Cite
|
Sign up to set email alerts
|

Pollen Selection for Drought Tolerance in Sunflower

Abstract: The drought resistance and genetic structure of F2 sporophytic populations for some morphological marker traits after pollen selection for water stress tolerance in F1 sunflower hybrids has been studied. The emasculated inflorescences were moistened with 10% and 20% of PEG 6000 solution in the experiments and with distilled water in the control. Freshly collected pollen was used for pollination after drying up the PEG solution on stigmas. F2 resulted seeds were germinated in 20% solution of PEG 6000 for a peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Such positive influence of pollen selection for heat stresses from the differential response of the pollen grains with reference to fertilization could be due to allelic differences in the pollen grains (Ravikumar, Patil, Soregaon, & Hegde, 2007). The effect of pollen selection for biotic and abiotic stress tolerance is clearly visible at the sporophytic stage of plants (Ravikumar et al., 2007; Ravikumar, Patil, & Salimath, 2003; Sacher, Mulcahy, & Staples, 1983; Totsky & Lyakh, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Such positive influence of pollen selection for heat stresses from the differential response of the pollen grains with reference to fertilization could be due to allelic differences in the pollen grains (Ravikumar, Patil, Soregaon, & Hegde, 2007). The effect of pollen selection for biotic and abiotic stress tolerance is clearly visible at the sporophytic stage of plants (Ravikumar et al., 2007; Ravikumar, Patil, & Salimath, 2003; Sacher, Mulcahy, & Staples, 1983; Totsky & Lyakh, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Selection at the pollen level has been proposed as a strategy to enrich the frequencies of genes associated with useful agronomic traits (Zamir & Vallejos, 1983). The effect of selection pressure under various biotic and abiotic stresses during the gametophytic generation was reported in several studies (Chi, Löffler, & Van Tuyl, 1999;Clarke et al, 2004;Domınguez et al, 2005;Frova, Portaluppi, Villa, & Goria, 1995;Maisonneuve, Hogenboom, & Den Nijs, 1986;Mandhu, Cresti, & Shivanna, 1992;Zamir, Tanksley, & Jones, 1982;Totsky & Lyakh, 2015) and has proved successful in increasing the frequency of tolerant progeny (Hormaza & Herrero, 1996;Ravikumar & Patil, 2002). Further, it is revealed that plants cope with heavy metal stress by making heritable changes in gene expression (Cong et al, 2019).…”
Section: Crop Sciencementioning
confidence: 95%
See 1 more Smart Citation
“…However, the reduction percentage is more intense in reproductive stages. Other researchers have referred to the formation of more unfilled seeds due to drought stress (Lyakh and Totsky, 2014; Totsky and Lyakh, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to water stress at critical stages such as germination, anthesis, and achene filling contributes up to 50% reduction in sunflower productivity (Kalarani et al 2004;Hussain et al 2008). Drought stress at the early growth stages reduces leaf area and stem elongation (Fatemi 2014), while at the anthesis stage, it causes pollen sterility and produces infertile achenes (Lyakh and Totsky 2014;Totsky and Lyakh 2015). Various studies have documented that water potential in sunflower decreases with increasing drought stress (Ghobadi et al 2013).…”
Section: Introductionmentioning
confidence: 99%